2010
DOI: 10.1007/s10803-010-1071-2
|View full text |Cite
|
Sign up to set email alerts
|

Teasing, Ridiculing and the Relation to the Fear of Being Laughed at in Individuals with Asperger’s Syndrome

Abstract: The present paper investigated the fear of being laughed at (gelotophobia) in relation to recalled experiences of having been laughed at in the past in individuals with Asperger's Syndrome (AS). About 45% of the individuals with AS (N = 40), but only 6% of the controls (N = 83) had at least a slight form of gelotophobia, which is the highest percentage ever found in the literature. Gelotophobia correlated with the frequency and severity of remembered teasing and mocking situations in the past. This indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 39 publications
3
59
1
1
Order By: Relevance
“…However, poor mind reading skills were associated not only with lower positive styles of humor, but also higher negative humor styles (Eriksson, this issue). One possible explanation for this is that poor mind reading skills lead to the insensitivity to read other people's emotions after using more aggressive humor, as discussed in Samson et al (2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, poor mind reading skills were associated not only with lower positive styles of humor, but also higher negative humor styles (Eriksson, this issue). One possible explanation for this is that poor mind reading skills lead to the insensitivity to read other people's emotions after using more aggressive humor, as discussed in Samson et al (2011).…”
Section: Resultsmentioning
confidence: 99%
“…There was a remarkably high percentage of gelotophobes, people who fear being laughed at, among the individuals with ASD (45% versus 6% in the control group). Moreover, individuals with ASD scored lower on gelotophilia (the joy of being laughed at), but did not differ on katagelasticism (the enjoyment of laughing at others), which is a more hostile form of humor (Samson et al 2011).…”
Section: Literature Overviewmentioning
confidence: 90%
“…In a recent study, a sample of patients with Asperger's syndrome was found to have the highest score in gelotophobia of any sample so far tested for their fear of being laughed at-about 45% yielded at least a slight expression of gelotophobia (Samson et al, 2011). In a different meaning from the current usage of the term, the Austrian physician Hans Asperger (1944) coined the patients later to be diagnosed with Asperger's syndrome with autistic psychopathy.…”
Section: Psychopathic Personality Traits and Dispositions Towards Ridmentioning
confidence: 99%
“…Ruch and Proyer developed a questionnaire for the assessment of these three dispositions (the PhoPhiKat-45), which discriminates well among the groups. It has already been used in a broad variety of studies from testing people with Asperger's Syndrome (Samson, Huber, & Ruch, 2011) to geriatric populations . Ruch and Proyer (2009a) describe katagelasticists with a somewhat rude and antisocial (not as a clinical category though) component.…”
Section: Psychopathic Personality Traits and Dispositions Towards Ridmentioning
confidence: 99%
See 1 more Smart Citation